2018
DOI: 10.1098/rsos.170978
|View full text |Cite
|
Sign up to set email alerts
|

Population, sex and body size: determinants of behavioural variations and behavioural correlations among wild zebrafish Danio rerio

Abstract: This study (1) investigated variation among populations and the effects of sex and body size on boldness, activity and shoal-association tendency among wild zebrafish, and (2) tested for existence of correlations between behaviours, controlling for sex and body size. Individuals across four natural populations were tested for general activity in a novel situation, number of predator inspections undertaken and tendency to associate with a conspecific shoal in the presence of predators. Results showed a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 58 publications
0
47
2
Order By: Relevance
“…Time spent in the center zone showed the greatest variability across weeks compared to stationary time and swimming speed. While several studies have found sex-specific behavioral variation of mating and aggressive behaviors 46,47,60 , we did not observe any sex differences in exploratory behavior.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Time spent in the center zone showed the greatest variability across weeks compared to stationary time and swimming speed. While several studies have found sex-specific behavioral variation of mating and aggressive behaviors 46,47,60 , we did not observe any sex differences in exploratory behavior.…”
Section: Discussioncontrasting
confidence: 99%
“…The local ecological factors that might have contributed to shaping the WC animals’ behavior are not known. It is possible that some population differences or behavioral correlations may only emerge under certain local environmental conditions 16,46,65 . Several studies that investigated wild zebrafish populations found that predation and water flow can explain population differences in behavioral correlations between boldness, aggression and activity 16,46 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Line (HSB, LSB), sex (male, female) and treatment group (0.75% ethanol, control) were used as between-subject variables. As the relationship between body size and locomotion is well documented 45,5456 , we included standard length as a covariate. Since we did not find a significant main effect of sex on behavior (top transitions: χ 2 (1) = 2.385, p = 0.123; top time: χ 2 (1) = 0.852, p = 0.356; distance: χ 2 (1) = 0.682, p = 0.409; and stationary time: χ 2 (1) = 0.092, p = 0.762) or gene expression ( gabra1: χ 2 (1) =0.036, p = 0.850; gabra2: χ 2 (1) = 0.382, p = 0.536; gadrd: χ 2 (1) = 1.942, p = 0.163; gabrg2: χ 2 (1) = 1.426, p = 0.232), we removed that variable from the analyses and used a simpler GLZ with line and treatment group as the only between-subject variables.…”
Section: Methodsmentioning
confidence: 99%